2014
DOI: 10.1016/j.freeradbiomed.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin VI oxidation in cerebrospinal fluid correlates with traumatic brain injury outcome

Abstract: Traumatic brain injury (TBI) patients would benefit from the identification of reliable biomarkers to predict outcomes and treatment strategies. In our study, cerebrospinal fluid (CSF) from patients with severe TBI was evaluated for oxidant stress-mediated damage progression after hospital admission and subsequent ventriculostomy placement. Interestingly, substantial levels of peroxiredoxin VI (Prdx6), a major antioxidant enzyme normally found in astrocytes, were detected in CSF from control and TBI patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…The 1-Cys peroxiredoxin-6 is localised to astrocytes and has been postulated to provide protection against membrane lipid peroxidation [40], whereas the 2-Cys peroxiredoxin-2 is present mainly in neurons [41]. In this study, we observed increased peroxiredoxin-6 levels in frontal grey matter following haloperidol administration, which may reflect an attempt to limit membrane lipid damage, or alternatively, an effect on astrocyte function.…”
Section: Discussionsupporting
confidence: 49%
“…The 1-Cys peroxiredoxin-6 is localised to astrocytes and has been postulated to provide protection against membrane lipid peroxidation [40], whereas the 2-Cys peroxiredoxin-2 is present mainly in neurons [41]. In this study, we observed increased peroxiredoxin-6 levels in frontal grey matter following haloperidol administration, which may reflect an attempt to limit membrane lipid damage, or alternatively, an effect on astrocyte function.…”
Section: Discussionsupporting
confidence: 49%
“…PRDX-6 is an antioxidant enzyme found primarily in astrocytes that may protect neuronal membranes and mitochondria from damage due to lipid peroxidation (38). PRDX-6 has been targeted in TBI due to the vulnerability of the brain to lipid peroxidation (38), and was recently uncovered as a candidate TBI biomarker in a rodent model using unsupervised autoimmune screening (39).…”
Section: Discussionmentioning
confidence: 99%
“…PRDX-6 is an antioxidant enzyme found primarily in astrocytes that may protect neuronal membranes and mitochondria from damage due to lipid peroxidation (38). PRDX-6 has been targeted in TBI due to the vulnerability of the brain to lipid peroxidation (38), and was recently uncovered as a candidate TBI biomarker in a rodent model using unsupervised autoimmune screening (39). Elevated PRDX-6 levels have been observed acutely across the spectrum of TBI in humans (40), and the restitution of PRDX-6 levels within 24 h of severe TBI in humans has been associated with improved recovery (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prx6 and GSTP in cerebrospinal fluid could be potential targets for therapeutic interventions in the TBI patients [94, 95]. …”
Section: Figurementioning
confidence: 99%